Current insights into the molecular mechanisms of hypoxic pre- and postconditioning using hypobaric hypoxia - Rybnikova, Elena; Samoilov, Mikhail (Frontiers in Neuroscience, 2015)
Exposure of organisms to repetitive mild hypoxia results in development of brain hypoxic/ischemic tolerance and cross-tolerance to injurious factors of a psycho-emotional nature. Such preconditioning by mild hypobaric hypoxia functions as a “warning” signal which prepares an organism, and in particular the brain, to subsequent more harmful conditions. The endogenous defense processes which are mobilized by hypoxic preconditioning and result in development of brain tolerance are based on evolutionarily acquired gene-determined mechanisms of adaptation and neuroprotection. They involve an activation of intracellular cascades including kinases, transcription factors and changes in expression of multiple regulatory proteins in susceptible areas of the brain. On the other hand they lead to multilevel modifications of the hypothalamic-pituitary-adrenal endocrine axis regulating various functions in the organism. All these components are engaged sequentially in the initiation, induction and expression of hypoxia-induced tolerance. A special role belongs to the epigenetic regulation of gene expression, in particular of histone acetylation leading to changes in chromatin structure which ensure access of pro-adaptive transcription factors activated by preconditioning to the promoters of target genes. Mechanisms of another, relatively novel, neuroprotective phenomenon termed hypoxic postconditioning (an application of mild hypoxic episodes after severe insults) are still largely unknown but according to recent data they involve apoptosis-related proteins, hypoxia-inducible factor and neurotrophins. The fundamental data accumulated to date and discussed in this review open new avenues for elaboration of the effective therapeutic applications of hypoxic pre- and postconditioning.